Pengetahuan ibu terkait stunting pada balita: A literature review - Fikriya, Aeni; Mirwanti, Ristina (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Stunting is a problem in children due to malnutrition which can impact all aspects of a child's life, so mothers have an important role in preventing and overcoming stunting. Purpose: To describe the results of research findings regarding maternal knowledge regarding stunting. Method: Systematic literature review research on articles on mothers' knowledge about stunting that have been published in the 2019-2024 period, and articles in English or Indonesian with respondents from mothers who have children under 5 years of age. The article collection process was carried out through searching several bases and search engines including Scopus, PubMed, Google Scholar and Crossref, then arranged using the PRISMA diagram to record each stage of the literature search. The search results found 19 articles that met the inclusion criteria. Result: Maternal knowledge is one of the factors related to the incidence of stunting in toddlers. However, the research results found that mothers' knowledge of toddler stunting was still inadequate. This is influenced by a number of aspects including: age, level of education, profession, and access to information. Conclusion: Maternal knowledge regarding stunting is still said to be low, so there is a need for policies and interventions to increase maternal knowledge regarding stunting. Keywords: Mother’s Knowledge; Stunting; Toddlers. Pendahuluan: Stunting merupakan permasalahan pada anak akibat kekurangan gizi yang dapat berdampak pada seluruh aspek kehidupan anak, sehingga ibu mempunyai peran penting dalam mencegah dan mengatasi stunting. Tujuan: Untuk mendeskripsikan hasil temuan penelitian mengenai pengetahuan ibu mengenai stunting. Metode: Penelitian tinjauan literatur sistematis terhadap artikel pengetahuan ibu tentang stunting yang telah terpublikasi pada rentang tahun 2019-2024 dan artikel dalam bahasa Inggris atau Indonesia dengan responden ibu yang mempunyai anak usia dibawah 5 tahun. Proses pengumpulan artikel dilakukan melalui penelusuran beberapa basis dan mesin pencari antara lain; Scopus, PubMed, Google Scholar, dan Crossref, disusun menggunakan diagram PRISMA dalam mencatat setiap tahapan pencarian literatur. Hasil penelusuran didapati 19 artikel yang masuk dalam kriteria inklusi. Hasil: Pengetahuan ibu merupakan salah satu faktor yang berhubungan dengan insiden stunting pada balita. Namun, hasil penelitian menemukan bahwa pengetahuan ibu terhadap stunting balita masih kurang memadai. Hal ini dipengaruhi oleh sejumlah aspek meliputi: usia, tingkat pendidikan, profesi, serta akses menuju informasi. Simpulan: Pengetahuan ibu terkait stunting masih dikatakan rendah, sehingga perlu adanya kebijakan dan intervensi dalam meningkatkan pengetahuan ibu terkait stunting. Kata Kunci: Balita; Pengetahuan Ibu; Stunting.